Dinâmica de sistemas acoplados a um reservatório com flutuações reduzidas via equação mestra - Marcelo Vitor da Cunha Pereira (2009)
The master equation is used here to describe the dynamics of a system which interacts with another one which possesses an infnite number of degrees of freedom, and which is usually called reservoir. Its utility is in making possible the simple description of this dynamics, relegating part of the information concerning the reservoir. In this master thesis the reservoir is considered as being described by a squeezed state, which is such that the dispersions associated with some of its operators arereduced. This results in a series of peculiar efects, measurable in principle. We expose theoretically these phenomena as well as the means of their detection. This makes necessary the use of several methods, which are commonplace in the study of open systems, like quasiprobability distributions, the quantum regression theorem and those which involve the resolution of partial diferential equations like the Fokker-Planck equation. The possibility of experimentally implementing the studied dynamics, which hasn't been done yet, is discussed superficially. The model however, describes concrete situations that until now have not been realized because of the technical dificulties involved.